Modern matrons and infection control practices: aspirations and realities - Koteyko, Nelya; Nerlich, Brigitte (2008)
Modern matrons were introduced in 2001 by the Department of Health to lead clinical teams in the prevention of healthcare associated infection. The facilitative role of modern matron requires both managerial and entrepreneurial skills and senior nurses are expected to lead by example, inspire, motivate and empower others, and thus conform to the `transformational leadership' style that foregrounds the importance of interpersonal and influencing skills. In this paper we identify problems that challenge this model of the modern matron and link them to possible problems in infection control. The study describes cases of difficulty in fulfilling leadership requirements because of organisational barriers to empowerment despite arguments to the contrary. Unless a significant budgetary responsibility is made part of the modern matron's role, personal skills (communication, problem solving) alone may not be sufficient to sustain it and may not lead to achieving control over infection, which was the initial trigger for instituting this role.